Economia popular y solidaria y bono de desarrollo humano en la provincia de El Oro. - Becerra Erraiz, Monica Alexandra; Guarnizo Pua, Didier Aldair (My University, 2021)
Popular and solidarity economies are vital in the current economic system of Ecuador, they fulfill vital functions in the rural productive fabric and in small territories as shown by the figures of agricultural businesses born of this economy, however, society, the large Companies and governments remain reluctant to really strengthen cooperation and solidarity for the actors of the popular and solidarity economy. The present work seeks to contribute to the knowledge of the local reality around the popular and solidarity economies, and of the beneficiaries of the human development bonus, for which, historical information on the origin and evolution of the bonus and of the number of beneficiaries for the province of El Oro, taking the ministerial reports and other institutions that are part of this new economy. It is possible to detect that there is an important growth of organizations of popular and solidarity economy, and of beneficiaries of the bonus with greater weight in women of the banana and commercial cantons of the province.
Las economías populares y solidarias son vitales en el sistema económico actual del Ecuador, cumplen funciones vitales en el tejido productivo rural y en los territorios pequeños tal como lo demuestran las cifras de negocios agropecuarios nacidos de esta economía, sin embargo, la sociedad, las grandes empresas y los gobiernos, siguen renuentes a fortalecer de manera real la cooperación y la solidaridad para los actores de la economía popular y solidaria. El presente trabajo busca aportar al conocimiento de la realidad local en torno a las economías populares y solidarias, y de los beneficiarios del bono de desarrollo humano, para lo cual, se recopila, clasifica y analiza información histórica del origen y evolución del bono y de la cantidad de beneficiarios para la provincia de El Oro, tomando los informes ministeriales y de otras instituciones que son parte de esta nueva economía. Se logra detectar que hay un crecimiento importante de organizaciones de economía popular y solidaria, y de beneficiarios del bono con mayor peso en las mujeres de los cantones bananeros y comerciales de la provincia.
Keywords: ECONOMÍA POPULAR Y SOLIDARIA; BONO DE DESARROLLO HUMANO; REFORMAS; SOLIDARIO